Insights into the Affordable Medicines Facility-malaria in Ghana: the role of caregivers and licensed chemical sellers in four regions. (December 2016) - Adjei, Andrew; Winch, Peter; Laar, Amos; Sullivan, David; Sakyi, Kwame; Stephens, Judith; Adjei, George; Boateng, Isaac; Aubyn, Vivian; Kubio, Chrysantus; Tuakli, Julliette; Vanotoo, Linda; et al.
Abstract Background The Affordable Medicine Facility-malaria (AMFm) was an innovative global financing mechanism for the provision of quality-assured artemisinin-based combination therapy (ACT) across both the private and public health sectors in eight countries in sub-Saharan Africa. This study evaluated the effectiveness of AMFm subsidies in increasing access to ACT in Ghana and documented malaria management practices at the household and community levels during the implementation of the AMFm. Methods This study, conducted in four regions in Ghana between January, 2011 to December, 2012, employed cross-sectional mixed-methods design that included qualitative and quantitative elements, specifically household surveys, focus group discussions (FGD) and in-depth interviews. Results The study indicated high ACT availability, adequate provider knowledge and reasonably low quality-assured ACT use in the study areas, all of which are a reflection of a high market share of ACT in these hard-to-reach areas of the country. Adequate recognition of childhood malaria symptoms by licensed chemical seller (LCS) attendants was observed. A preference by caregivers for LCS over health facilities for seeking treatment solutions to childhood malaria was found. Conclusions Artemisinin-based combination therapy with the AMFm logo was accessible and affordable for most people seeking treatment from health facilities and LCS shops in rural areas. Caregivers and LCS were seen to play key roles in the health of the community especially with children under 5 years of age.